Can Electronic Tax Invoicing Improve Tax Compliance? : A Case Study of the Republic of Korea's Electronic Tax Invoicing for Value-Added Tax - Lee, Hyung Chul (World Bank, Washington, DC, 2016)
This paper reviews the Republic of Korea's experience with electronic tax invoices for its value-added tax regime from the perspectives of tax policy makers and administrators. The paper evaluates Korea's implementation of electronic tax invoicing and analyzes its effect on tax compliance through enhanced transparency of business transactions and taxpayer services. First implemented in 2011, mandatory electronic tax invoicing has been credited with lowering tax compliance costs and raising the transparency of business transactions. Effective policy design and implementation have contributed to the country's success with electronic tax invoicing. Measured in transaction value, the electronic tax invoice adoption rate reached 99.8 percent in the first year and rose to 99.9 percent by 2013, compared with 15 percent before electronic tax invoicing became mandatory. According to a survey of taxpayers and tax practitioners in Korea that was conducted as part of this research study, 69.4 percent of the respondents agreed or strongly agreed that mandatory electronic tax invoicing has contributed to curbing value-added tax evasion by raising transaction transparency, and 72.9 percent agreed or strongly agreed that it has improved taxpayer service by facilitating the convenience of tax filing or automating the issuance of invoices. The review of Korea's experiences gives credence to the contention that well-planned and well-executed compulsory electronic tax invoices can materially enhance tax compliance through significant institutional and perceptual changes in tax administration.